The Comparison of Diagnostic Modalities in Patients with Postmenopausal Uterine Bleeding - Çöğendez, Ebru; Aran, Turhan; Çam, Çetin; Karateke, Ateş (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: To investigate the diagnostic values of dilatation and curettage, transvaginal sonography, sonohysterography and hysteroscopy in diagnosing the intracavitary pathologies in women with postmenopausal bleeding. STUDY DESIGN: 30 women diagnosed as postmenopausal bleeding were included into the study. All patients underwent transvaginal sonography and sonohysterography as primary evaluation; hysteroscopy and dilatation and curettage were performed immediately in seven days after primary evaluation. RESULTS: No woman with an endometrial thickness of ≤ 5mm was diagnosed as having endometrial cancer. In women with an endometrial thickness of ≤ 5mm, transvaginal sonography showed a sensitivity 100%, specificity 48%, positive predictive value (PPV) 18% and negative predictive value (NPV) 100% in detecting neoplastic changes. The sensitivity, specificity, PPV, NPV and accuracy of sonohysterography for detecting all endometrial pathologies were 100%, 73%, 54%, 100% and 80% respectively. These findings for hysteroscopy were 100%, 78%, 58%, 100% and 83% respectively. CONCLUSION: Transvaginal sonography as the primary tool in diagnosing postmenopausal lesions should be supported with sonohysterography. Patients with focal intracavitary lesion diagnosed on sonohysterography should undergone hysteroscopic evaluation enabling direct visualization and sampling of the endometrial cavity as the gold standard.